2018
DOI: 10.1021/acssuschemeng.7b04840
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Persulfate at Waste Heat Temperatures for Humic Acid Degradation

Abstract: Humic acid (HA) as a major constituent of natural organic matter (NOM) in raw water presents major challenges to drinking water production including membrane fouling and serving as a precursor for the production of disinfection byproducts (DBPs). This study demonstrates the feasibility of HA degradation by heat-activated persulfate (PS) mainly at a waste heat temperature of 40 °C, but also at 60 and 90 °C in which ∼70% TOC loss was achieved within 168, 24, and 1 h, respectively. The use of waste heat for water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Therefore, the intrinsic bactericidal effect at 50 o C plays a minor role and the bacterial inactivation is mainly due to the effect of PS, which also suggests that 50 o C is the effective temperature for the activation of PS for bacterial inactivation if no light is used. This result is consistent with previous reports that 40-50 o C is the effective temperature for heat activation of PS for the degradation of organic pollutants (Ike et al 2018). In addition, the 8.78×10 -4 min -1 for o C and 50 o C, respectively.…”
Section: Effect Of Temperature For Ps Activationsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, the intrinsic bactericidal effect at 50 o C plays a minor role and the bacterial inactivation is mainly due to the effect of PS, which also suggests that 50 o C is the effective temperature for the activation of PS for bacterial inactivation if no light is used. This result is consistent with previous reports that 40-50 o C is the effective temperature for heat activation of PS for the degradation of organic pollutants (Ike et al 2018). In addition, the 8.78×10 -4 min -1 for o C and 50 o C, respectively.…”
Section: Effect Of Temperature For Ps Activationsupporting
confidence: 94%
“…As well known, PS can be activated by heat (Ike et al 2018, Waldemer et al 2007, Zrinyi and Pham 2017. Since VL irradiation may cause initial temperature rise during the reaction process, to test the possibility of PS activation by heat or by VL irradiation, the effect of different temperatures on the PS activation was studied first for bacterial inactivation In contrast, all the 7.0 log of cells can be completely inactivated within 60 min with PS addition.…”
Section: Effect Of Temperature For Ps Activationmentioning
confidence: 99%
“…49 Third, HA is itself a scavenger of SO 4 c À and $OH; this, it will consume reactive radicals in increasing amounts. 50,51 Thus, under the conditions of adequate oxidant, a higher HA concentration requires a longer period to reach the identical removal ratio. The above results are similar to those of many studies about organics removal by persulphate activation.…”
Section: Reaction Parametersmentioning
confidence: 99%
“…Meanwhile, compared with the nonselective and high oxidative potential (2.8 eV) hydroxyl radical ( • OH)-based AOPs, the sulfate radical (SO 4 •– )-based AOPs were also increasingly a concern due to high oxidative potential (2.5–3.1 eV), a wide pH range (2–8), and a much longer half-life (∼30–40 μs). Persulfates, including peroxydisulfate (PDS) and peroxymonosulfate (PMS), can be activated to generate both hydroxyl radicals ( • OH) and sulfate radicals (SO 4 •– ), making them promising candidates for controlling membrane fouling in electrocatalysis without causing secondary pollution. , However, the oxidation mechanism and performance of PDS and PMS differ in the degradation of organic matter due to their distinct physicochemical properties. Previous studies have revealed that in the electro-activation process, PDS primarily oxidized carbamazepine through the generation of free radicals and a direct electron transfer pathway, whereas free radicals played a dominant role in the electro-activation of PMS. , For this reason, PDS and PMS may give rise to divergent outcomes in the oxidation process. However, even slight variations in the oxidation pathway can lead to significantly different interactions with membrane fouling.…”
Section: Introductionmentioning
confidence: 99%